Forty years of context effect research in marketing: a bibliometric analysis - Susanne Jana Adler; Martina Katharina Schöniger; Marcel Lichters; Marko Sarstedt (Journal of Business Economics, 2023)
Research on context effects shows that the composition of choice sets and choice framing strongly influences consumer decision-making. Researchers have identified various context effect types and provide insight into their antecedents, consequences, and mechanisms of action. However, the research on context effects is spread across several fields, making it difficult to grasp the entire scope. Reviews focusing on specific effect types can facilitate rigorous research and publication practices, but they focus primarily on prominent context effects, neglecting others. Furthermore, those reviews do not provide insight into the structure of scholarly networks that result from research collaborations and shape, generate, distribute, and preserve the intellectual knowledge of the context effect domain. Addressing these issues, we present a large-scale bibliometric analysis of the field, that helps navigate the context effect landscape, highlights its themes, and identifies knowledge gaps. An interactive web application also allows for our analyses to be customized and extended.
Keywords: 650; Bibliometric analysis; Context effect; Attraction effect; Compromise effect; Asymmetric dominance effect; Phantom decoy effect